Increasing motivation through active-learning strategies - Arnold, Craig; Winberry, Kathy (California : Lee Canter & Associates, 1995)
In the first section of the video, presenter will address several strategies for motivating students through questioning, and in the second section, presenter touch on involvement strategies
Video is accompanied by 1 leader's manual
Executive producer, Lee Canter
Narrator: Ron Snow
Host: Lee Canter
Keywords: Learning, Psychology of; Motivation in education; Achivement motivation in children